Fine needle aspiration for evaluation of breast masses - Benjaporn Chaiwun (2018)
PURPOSE OF REVIEW: Fine needle aspiration has been used for many years as a diagnostic tool for breast lesions, with high sensitivity and specificity. There is controversy as to whether this technique should be replaced by other diagnostic procedures such as core biopsy. This review aims to re-evaluate the usefulness of breast fine needle aspiration. RECENT FINDINGS: During the past 10 years many institutions have replaced fine needle aspiration by core biopsy and related techniques such as vacuum-assisted core biopsy and advanced breast biopsy instrument action. Other institutions continue to use fine needle aspiration as a first line of investigation for breast lesions. This technique is especially useful in radiologically benign lesions and when combined with image guidance. The use of the 'triple test' (combined cytologic, clinical and radiologic findings) decreases false-negative and false-positive results. SUMMARY: Fine needle aspiration continues to be an acceptable and reliable procedure for the preoperative diagnosis of breast lesions, particularly in developing countries, and when used as part of the 'triple test'. Accurate diagnosis requires experience in both aspiration technique and specimen interpretation. Clinicians should be mindful of the limitations of the technique. The choice between fine needle aspiration and core biopsy should be individualized for the patient. © 2007 Lippincott Williams & Wilkins, Inc.